2018
DOI: 10.3390/app8122408
|View full text |Cite
|
Sign up to set email alerts
|

Advancing High-Speed Transmissions over OCDMA Networks by Employing an Intelligently Structured Receiver for Noise Mitigation

Abstract: We propose an intelligently structured receiver to achieve high-speed transmissions over optical code-division multiple access (OCDMA) networks. Employing spectral-amplitude coding (SAC) reduces multiuser interference (MUI) in OCDMA, but the network bit-rate is limited by phase-induced intensity noise (PIIN) coming from the incoherency of light sources. To mitigate PIIN, the receiver performs interference estimations and regenerations through consecutive stages. The MUI is removed by subtracting the estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…DS-CDMA is much more popular than FH-CDMA commercially. 25,26 A major advantage of frequency hopping is that it can be implemented over a much larger frequency band than it is possible to implement DS spreading, and the band can be noncontiguous. Another major advantage is that frequency hopping provides resistance to multiple-access interference while not requiring power control to prevent near-far problems.…”
Section: Gfsk-modulated Fhss Signal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…DS-CDMA is much more popular than FH-CDMA commercially. 25,26 A major advantage of frequency hopping is that it can be implemented over a much larger frequency band than it is possible to implement DS spreading, and the band can be noncontiguous. Another major advantage is that frequency hopping provides resistance to multiple-access interference while not requiring power control to prevent near-far problems.…”
Section: Gfsk-modulated Fhss Signal Modelmentioning
confidence: 99%
“…In fact, SS or CDMA has only two forms, DS‐CDMA and FH‐CDMA. DS‐CDMA is much more popular than FH‐CDMA commercially 25,26 . A major advantage of frequency hopping is that it can be implemented over a much larger frequency band than it is possible to implement DS spreading, and the band can be noncontiguous.…”
Section: Gfsk‐modulated Fhss Signal Modelmentioning
confidence: 99%
“…Some studies have reported a novel multiplex technique, namely optical code division multiple access (OCDMA) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. OCDMA employs CDMA techniques in optical fiber communication environments.…”
Section: Introductionmentioning
confidence: 99%
“…Because phase shifts must be identified on a coder spectral response, their entire structure is relatively complex. To improve system performance, some researchers have proposed an intelligently structured receiver to suppress noise effects and a semiconductor optical amplifier (SOA) to mitigate temperature variation effects on links [ 16 , 17 ]. In 2018, Yen et al presented Walsh–Hadamard-code-based OCDMA techniques with moderate security for applications in WOC environments [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optical code-division multiple access (OCDMA), providing high speed and security communications in access networks, has the potential to support all-optical processing [9][10][11]. The obtained label numbers in OCDMA are more flexible than the ones in wavelength-division multiplexing (WDM), and recent literature has demonstrated that OCDMA is compatible with the labeling scheme in OPS [9][10][11][12]. Converting packet labels into optical codes can be categorized into two methods, the explicit and implicit labels, according to the packet structure [12].…”
Section: Introductionmentioning
confidence: 99%